Piloting of a minimum data set for older people living in care homes in England: protocol for a longitudinal, mixed-methods study - Claire Goodman; Julienne Meyer; Barbara Hanratty; Lisa Irvine; Arne Timon Wolters; Richard James Brine; Elizabeth Crellin; Gizdem Akdur; Adam Gordon; Anne Killett; Jennifer Burton; Ann-Marie Towers; et al. (BMJ Open)
Introduction Health and care data are routinely collected about care home residents in England, yet there is no way to collate these data to inform benchmarking and improvement. The Developing research resources And minimum data set for Care Homes’ Adoption and use study has developed a prototype minimum data set (MDS) for piloting.Methods and analysis A mixed-methods longitudinal pilot study will be conducted in 60 care homes (approximately 960 residents) in 3 regions of England, using resident data from cloud-based digital care home records at two-time points. These will be linked to resident and care home level data held within routine National Health Service and social care data sets. Two rounds of focus groups with care home staff (n=8–10 per region) and additional interviews with external stakeholders (n=3 per region) will explore implementation and the perceived utility of the MDS. Data will be assessed for completeness and timeliness of completion. Descriptive statistics, including percentage floor and ceiling effects, will establish data quality. For validated scales, construct validity will be assessed by hypothesis testing and exploratory factor analysis will establish structural validity. Internal consistency will be established using Cronbach’s alpha. Longitudinal analysis of the pilot data will demonstrate the value of the MDS to each region. Qualitative data will be analysed inductively using thematic analysis to understand the complexities of implementing an MDS in care homes for older people.Ethics and dissemination The study has received ethical approval from the London Queen’s Square Research Ethics Committee (22/LO/0250). Informed consent is required for participation. Findings will be disseminated to: academics working on data use and integration in social care, care sector organisations, policy makers and commissioners. Findings will be published in peer-reviewed journals. Partner NIHR Applied Research Collaborations, the National Care Forum and the British Geriatrics Society will disseminate policy briefs.